2012
DOI: 10.1080/10496491.2012.668431
|View full text |Cite
|
Sign up to set email alerts
|

Examining Third-Person Perceptions in the Context of Sexually Oriented Advertising

Abstract: A limited amount of research has been undertaken to investigate third-person perceptions as persuasion in the context of sexually oriented advertising. This study examined whether sexually oriented advertising and gender differences would yield significant influences on third-person perceptions and whether participants' sexual cognition would moderate their third-person perceptions. Results showed that sexually oriented advertising, gender differences, and sexual cognition were significant factors that dominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Evidence of TPE in people's response to negative messages ranges from susceptibility to defamatory messages (Cohen et al 1988), violent and misogynic rap lyrics (McLeod, Eveland, and Nathanson 1997), persuasive influence of media messages (Perloff 2002), pornography on the internet (Lee and Tamborini 2005;Wu and Koo 2001), alcohol product placements (Shin and Kim 2011) and sexual advertising (Pan, Meng, and Zhou 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of TPE in people's response to negative messages ranges from susceptibility to defamatory messages (Cohen et al 1988), violent and misogynic rap lyrics (McLeod, Eveland, and Nathanson 1997), persuasive influence of media messages (Perloff 2002), pornography on the internet (Lee and Tamborini 2005;Wu and Koo 2001), alcohol product placements (Shin and Kim 2011) and sexual advertising (Pan, Meng, and Zhou 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Here, a positive attitude refers to relatively liberal individuals who are comfortable with sexual stimuli, whereas a negative attitude refers to relatively conservative individuals who are uncomfortable with sexual stimuli. Further, people's current beliefs and perceptions about the influence of communication are predicted to be an important determinant of their perception of these media messages (Pan, Meng, and Zhou 2012). Current beliefs and biases toward an ad will influence the perception of the ad.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…To test validity, exploratory factor analysis was performed using the maximum likelihood extraction and promax rotation method. To measure thirdperson perception, participants were asked to respond to two sets of statements (Pan, Meng, and Zhou 2012) regarding the self and others (defined as "other students at the university").…”
Section: Measures Validity and Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on persuasive messages can be found in the third-person scholarship in various contexts of television talk show, 42 sexually oriented advertising, 43 political attack advertising, 44 and online pornography legislation, 45 but they have not examined the role of third-person perception in the context of cosmeceutical product-relevant messages. Thus, it is essential to examine how third-person perception would operate after exposure to cosmeceutical product advertisement.…”
Section: Third-person Perceptionmentioning
confidence: 99%